2020
DOI: 10.1088/1361-648x/ab88f4
|View full text |Cite
|
Sign up to set email alerts
|

Shape analysis of random polymer networks

Abstract: We analyze conformational properties of branched polymer structures, formed on the base of Erdös-Rényi random graph model. We consider networks with N = 5 vertices and variable parameter c, that controls graph connectedness. The universal rotationally invariant size and shape characteristics, such as averaged asphericity A 3 and size ratio g of such structures are obtained both numerically by application of Wei's method and analytically within the continuous chain model. In particular, our results quantitative… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…Numerous studies on network structure and elasticity can be found in the literature [81,99,101,[135][136][137][138][139][140][141][142]. In this study, I apply the particle-based Monte-Carlo simulation SOMA to study gelation and microphase separation of randomly crosslinked symmetric diblock copolymers for various crosslink densities and preparation conditions.…”
Section: Chaptermentioning
confidence: 99%
“…Numerous studies on network structure and elasticity can be found in the literature [81,99,101,[135][136][137][138][139][140][141][142]. In this study, I apply the particle-based Monte-Carlo simulation SOMA to study gelation and microphase separation of randomly crosslinked symmetric diblock copolymers for various crosslink densities and preparation conditions.…”
Section: Chaptermentioning
confidence: 99%